Aquatic photolysis of the pharmaceutical ambroxol: The role of 2, 4-dibromoaniline chromophore and heavy atom effect of bromine. (1st November 2022) - Wang, Lixiao; Xu, Haiyan; Lu, Junhe; Chovelon, Jean-Marc; Ji, Yuefei
Highlights: 2, 4-Dibromoaniline is the core chromophore of ambroxol. Exposure to UV254 resulted in debromination of ambroxol and 2, 4-dibromoaniline. The para -Br is more vulnerable toward photo-debromination. A total of 12 photoproducts were identified. Bioluminescence inhibition assay revealed that photoproducts were not toxic. Abstract: As one of the most effective expectorant class drugs, ambroxol (AMB) has been frequently used to treat acute and chronic bronchitis. Extensive use and human excretion result in the widespread occurrence of AMB in wastewater. Herein, we reported the photolysis of AMB in aqueous solution upon 254 nm ultraviolet radiation (UV254 ). Spectroscopic characterization showed that 2, 4-dibromoaniline (DBA) moiety is the core chromophore of AMB. Quantum yield of DBA changed little at pH 4.0 - 9.0; however, AMB showed higher quantum yield at pH > 8.0. Both DBA and AMB have high photoreactivity, which can be attributed to the "heavy atom" effect of bromine substituents. The photolysis of AMB occurred through photoreduction, photoionization, photonucleophilic substitution, side-chain cleavage, and coupling reactions. Both AMB and DBA underwent debromination with yields reaching 80% under 3200 mJ cm −2 UV fluence. Photo-debromination occurred preferentially at the para -position. The presence of natural organic matter inhibited the photodegradation, mainly due to the light-screening effect. The photolysis of AMB was slightly enhanced in the presence of NO3 − likely due to radical-induced oxidation. Bioluminescence inhibition assay revealed that photoproducts were not toxic. The results show that UV254 radiation with fluences relevant to advanced oxidation processes was effective for the abatement of AMB in wastewater. However, UV254 treatment of wastewater containing higher concentrations (˃ μg L −1 ) of AMB should be done with caution because the released Br − can be converted to toxic brominated disinfection byproducts and bromate in subsequent oxidation process. Graphic abstract: Image, graphical abstract